Kesantunan Bertutur oleh Orang Tua kepada Anak di Lingkungan Rumah Tangga - Kusno, Ali (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2014)
Provoking a model of politeness for their children, parent need to consider some principles of politeness. They are: maxim of wisdom, maxim of philanthrophy, maxim of appreciation, maxim of simplicity, maxim of democracy, and maxim of sympaty. Parent sometimes use the imperative utterances to their children. The usage of linguistics politeness of imperative utterances to the children need to consider the principles of politeness in using the imperative utterances. Some techniques can be applied to create a polite utterance, they are: the usage of adequate duration, the usage of appropriate sequence of the utterance, the intonation and gestures and, the usage of politeness markers.